Users’ perception of the Community Centers for physical activity from two cities in Ceará, Brazil - Lucetti, Maria Dayanne Luna; Santana, Valeska Virgínia Freitas de; Vidal, Eglídia Carla Figueiredo; Silva Filho, José Adelmo da; Pinto, Antonio Germane Alves (ABCS Health Sciences, 2020)
Introduction: The practice of physical activity provides benefits to health and, consequently, to people's quality of life, helping to promote health and prevent disease. Objective: To understand the perception of the users about the physical activity poles with emphasis on the structure, functioning and professional support in health promotion practices. Methods: This is an exploratory qualitative approach. The locus of the study involved two community poles of physical activity, one of them being the Health Academy Program (PAS) in different municipalities. The sample counted on 15 participants, being 5 of one pole and 10 of the other to which the PAS works. Data were collected through the semistructured interview and synthesized through thematic analysis. Results: Disagreements were observed in relation to the statements of the population about the community physical activity pole and on the pole of the Health Academy Program. It was evidenced the absence of qualified professionals to assist in the practice of the exercises and to make necessary orientations regarding the practice of the activity. It was also noted that the distance between the residence and the pole can be a potential incentive or discouraging, since the location of the distant poles of the homes makes it difficult for the population to routinely adhere to physical activities. Conclusion: Prevalence among the interviewees of dissatisfaction about the organization and functioning of the community poles of physical activity.